Introduction - Chris Greenough (University of Sheffield, 2021)
This special edition is a form of pride. It is a celebration of thirty years since the birth of queer theory. Of course, being queer, this was no normative conception or birth. More of an artificial insemination and fusion of gene pools, characterised by anarchy, activism, subversion, deconstruction, alongside identitarian and non-identitarian concerns. Queer theory transcends many disciplines. Raising suspicion from those concerned with normative ideas of scholarship, queer oscillates between delighting the academy with its offer of dense critical theory and radical undoing, yet it also disgusts traditionalists who hold allegiances to normative scholarship. With its agenda of subversion and playful parody, it is no coincidence that the term “queer theory” was first coined as a joke. Teresa de Lauretis had heard the term “queer” reclaimed on the streets by gay activists, and, as David Halperin comments, “she had the courage, and the conviction, to pair that scurrilous term with the academic holy word ‘theory.’” Here, the authors of this special edition share the same courage and conviction to pair the term with biblical texts.